The Effectiveness of Badminton Learning Through the Badminton Stroke Technique Learning Method for Students of Universitas Bung Hatta - Alfiqroam , Alfiqroam Kumar; Suud Cahyo Alben, Ary; Effendi, Heri; Pramadita, Yulia; Rizka Aprilia, Cici; Ucale Douw, Ronaldo (Universitas Majalengka, 2025)
This study aims to evaluate the effectiveness of badminton instruction through a more engaging and interactive badminton stroke technique learning method for students at Universitas Bung Hatta, Padang, during the 2023-2024 academic year. The research employed an experimental design with pre-test and post-test assessments, involving 14 students from the Physical Education, Health, and Recreation Study Program enrolled in the badminton course. The instruments used in this study included practical skill tests and theoretical tests to measure the students' learning outcomes before and after the implementation of the more engaging and interactive badminton stroke technique method. The results indicated that the average pre-test score was 80.14, with a standard deviation of 4.13, while the average post-test score was 81.27, with a standard deviation of 3.95. This reflects an increase of 1.13 points (1.41%) in the students' average score after the intervention, demonstrating that the badminton stroke technique instruction was effective in improving the students' skills. The t-test analysis revealed that the computed t-value (3.52) was greater than the critical t-value (1.770), indicating that the research hypothesis is supported. Consequently, it can be concluded that the implementation of the more engaging and interactive badminton stroke technique learning method significantly enhances the effectiveness of badminton instruction for students at Universitas Bung Hatta, Padang.